2016
DOI: 10.1103/physrevb.93.184507
|View full text |Cite
|
Sign up to set email alerts
|

Unusual superconducting isotope effect in the presence of a quantum criticality

Abstract: We discuss the possible connection between superconductivity (SC) and quantum critical points (QCP) for any QCP that is tunable by isotopic mass substitution. We find a distinct contribution to the isotope exponent, due to the proximity to a QCP, which can be used as an experimental signature for the relation between SC and QCP. The relation is demonstrated in a scenario where the SC pairing is due to modes related to a structural instability. Within this model the isotope exponent is derived in terms of micro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…[19], FE modes close to a quantum critical point (QCP) were suggested as the source of SC and used to explain the vanishing SC for increased levels of doping. An unusual isotope effect was proposed as a method to study the phenomenology of the critical behavior [20] and was experimentally observed [21], supporting the connection of SC to the QCP. The coexistence of FE and SC was observed [22] and strain was also proposed as a tuning parameter [23] and experimentally investigated [24].…”
mentioning
confidence: 86%
“…[19], FE modes close to a quantum critical point (QCP) were suggested as the source of SC and used to explain the vanishing SC for increased levels of doping. An unusual isotope effect was proposed as a method to study the phenomenology of the critical behavior [20] and was experimentally observed [21], supporting the connection of SC to the QCP. The coexistence of FE and SC was observed [22] and strain was also proposed as a tuning parameter [23] and experimentally investigated [24].…”
mentioning
confidence: 86%
“…Electron-doped STO is one of the most dilute superconductors known [103,104], and most likely a non-BCS mechanism is necessary for its explanation More recently a gate-tunable insulatingsuperconducting transition has been observed in an STO weak link [105], again pointing to anomalous behavior in this material. The dependence of the superconducting T c on the percentage of 18 0 in the STO is an active topic of theoretical [106,107] and experimental [108] research. We will return to the question of superconductivity in STO in the "Open Questions" section.…”
Section: The Case Of Srt Io 3 To Datementioning
confidence: 99%
“…For example, Raman scattering found that the hardening of the FE soft mode in the dilute metal is indistinguishably similar to what is seen in the insulator [21]. The anomaly in resistivity was found to terminate at a threshold carrier density (n * ), near which the superconducting transition temperature was enhanced [21] providing evidence for a link between superconducting pairing and ferroelectricity, a subject of present attention [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 98%